2010
DOI: 10.1183/09031936.00068310
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of azithromycin to prevent chronic rejection after lung transplantation

Abstract: Azithromycin reduces airway inflammation and improves forced expiratory volume in 1 s (FEV1) in chronic rejection or bronchiolitis obliterans syndrome (BOS) after lung transplantation (LTx). Azithromycin prophylaxis might prevent BOS.A double-blind randomised controlled trial of azithromycin (n540) or placebo (n543), initiated at discharge and administered three times a week for 2 yrs, was performed in 2005-2009 at the Leuven University Hospital (Leuven, Belgium). Primary end-points were BOS-free and overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(185 citation statements)
references
References 30 publications
7
173
3
2
Order By: Relevance
“…The use of azithromycin in a randomized controlled trial has been shown to slow the progression of CLAD, potentially through its anti-inflammatory, antibiotic, or promotility effects, but the exact mechanism is unclear (Yates et al 2005;Murphy et al 2008;Vos et al 2011). Switching classes of immunosuppression may be of some benefit in slowing progression of the disease, but no therapy has yet been shown to reverse the disease process.…”
Section: Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…The use of azithromycin in a randomized controlled trial has been shown to slow the progression of CLAD, potentially through its anti-inflammatory, antibiotic, or promotility effects, but the exact mechanism is unclear (Yates et al 2005;Murphy et al 2008;Vos et al 2011). Switching classes of immunosuppression may be of some benefit in slowing progression of the disease, but no therapy has yet been shown to reverse the disease process.…”
Section: Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…In fact, a randomized placebo controlled prevention trial with azithromycin initiated at hospital discharge following transplantation has shown that patients taking azithromycin demonstrate better pulmonary function, as well as decreased BAL neutrophilia and lower CLAD prevalence (35). A recent post-hoc analysis of this trial revealed that these long-term beneficial effects persisted and that azithromycin was able to significantly postpone the development of CLAD (36).…”
Section: Treatmentmentioning
confidence: 99%
“…[5] Prophylactic AZI has also been evaluated as an intervention to prevent BOS in both LTX and HCT recipients. Vos et al [13] published a placebo-controlled RCT that demonstrated significantly improved, BOS-free survival and significantly better preservation of FEV1 in the AZI treatment arm when AZI started prior to hospital discharge following LTX. Additionally, longer term analysis of the treatment arms from this same RCT showed that prophylactic AZI was associated with significantly improved CLAD-free survival, pulmonary function, and functional exercise capacity versus the placebo group.…”
Section: How Can Bos Be Treated?mentioning
confidence: 99%